0343 In-person Expert Pillow Fitting Process Improves Sleep Quality and Duration. (25th May 2022) - Rus, Holly; Danoff-Burg, Sharon; Weaver, Morgan; Rodriguez, Rodolfo; Gavrilova, Larisa; Burke, Colin; Carmon, Kiara; Ledesma, Duvia Lara; Gottlieb, Elie
Abstract: Introduction: The myriad of anecdotal claims about the benefits of different pillow types may complicate consumers' ability to find a pillow that can support better sleep. Services that provide consumers with personalized recommendations may address this problem. This study examined the sleep of research participants using pillows selected during an in-store pillow fitting process compared to using their original pillows. Methods: Healthy adults (71% female, ages 21-59) who reported interest in a new pillow participated in a 9-week field study using a pre-post intervention design. The intervention consisted of being guided through the Mattress Firm in-store pillow fitting process to be paired with a pillow that provided the best fit and support based on body type and sleeping position preferences. During the 4-week baseline period, participants used their regular pillow. Once they were fit for their new pillow, participants slept with that pillow for 5 weeks, including a 1-week adjustment period. Sleep was measured objectively using SleepScore Max every night and by daily and pre-post self-report. Multilevel regression and paired t-tests and were used to test for statistical significance. Results: There were 722 nights of tracked sleep across participants (n=17). Objective sleep measurements showed nightly improvement in SleepScore, a measure of objective sleep quality (p=.003), longer time in bed (+13 minutes, p=.034), longer sleep duration (+16 minutes, p=.010), a lower proportion of the night awake after falling asleep (p=.009), and better sleep maintenance (p=.009). In addition, participants got more deep sleep (+5.6 minutes, p=.017) and showed improved BodyScore, a measure of deep sleep (p=.031). Self-reported measures showed improvements in pillow comfort and overall comfort in bed; perceived ability to sleep through the night; perceived reduction in number of awakenings and amount of time awake at night; better overall sleep quality; and feeling more well-rested in the morning when using the fitted pillows compared to baseline (all ps <.05). Conclusion: Objective and self-reported sleep improved among healthy adults using a pillow selected by an expert, in-person pillow fitting process. The results suggest that a pillow fitting process can improve sleep by helping individuals find a pillow that provides a personalized fit and optimal comfort. Support (If Any): Mattress Firm INC